2005
DOI: 10.1007/s00795-004-0270-3
|View full text |Cite
|
Sign up to set email alerts
|

cDNA microarray analysis after laser microdissection in proliferating islets of partially pancreatectomized mice

Abstract: With islet transplantation having grown in popularity since the introduction of the Edmonton protocol, how to secure an unlimited source of islets has become an urgent problem. To resolve this problem, techniques to induce or proliferate islets are urgently required. To achieve this goal, gene expression analysis using a cDNA microarray in islets of partially pancreatectomized mice, in which the remaining islets regenerate and proliferate with insulin secretion and glucose responsiveness, provides us with valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This demonstrated that the protocol for cDNA amplification provided reliable measures of the relative transcript abundances. Although this method has been successfully applied in several small-scale expression studies [ 29 - 35 ], to our knowledge, the use of this technique has not been reported with commercial photolithographically synthesized arrays.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrated that the protocol for cDNA amplification provided reliable measures of the relative transcript abundances. Although this method has been successfully applied in several small-scale expression studies [ 29 - 35 ], to our knowledge, the use of this technique has not been reported with commercial photolithographically synthesized arrays.…”
Section: Resultsmentioning
confidence: 99%
“…RNA amplification have been extensively used by several groups (Klur et al, 2004;Wu et al, 2006;Murphy et al, 2005;Coco et al, 2005;Schlomm et al, 2005;Katsuta et al, 2005) when combining LMD and microarray hybridization to identify characteristic genes or gene expression patterns crucial to the understanding of tissue function in normal and diseased states, because the RNA amount isolated from the microdissected specimens (usually in the pg or low ng range) is not sufficient for microarray analysis (several lg are required). Now RNA amplification systems are emerging as method for preparing amplified cDNA from total RNA for gene expression analysis using real-time quantitative PCR (Kurn et al, 2005) for global gene expression analysis from very small samples.…”
Section: Rnamentioning
confidence: 99%
“…Both processes can occur, nevertheless, in absence of 'true' islet regeneration. Among these factors, some endogenous proteins were identified by high-throughput transcriptome and proteome screens of regenerating pancreata [87][88][89][90]. Whole pancreatic extracts after injury appear to promote b-cell mass augmentation in mice treated with STZ [91,92].…”
Section: Box 2 Biomolecules For B-cell Regenerationmentioning
confidence: 99%